Karakter Fisik dan Kimia Buah Pepaya pada Stadia Kematangan Berbeda - Ketty Suketi; Roedhy Poerwanto; Sriani Sujiprihati; , Sobir; Winarso Drajad Widodo (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2010)
The objective of the experiment was to investigate the physical and chemical characteristics of three stadia of maturity based on a range of peel color from green to yellow or based on percentage of the yellow area of fruit peel (stadium 1 = 25-49 % yellow, stadium 2 = 50-74 % yellow, and stadium 3 = above 75 % yellow) on six genotypes of papaya. Each genotype exhibited different days to maturity for each stadium. The fruits of stadium 1, 2 and 3 for IPB 1 were picked at 130, 135, and 140 days after anthesis (DAA); IPB 10A at 160, 165, and 170 DAA; IPB 1 x PB 174 at 135, 140 and 145 DAA; while PB 174, IPB 1 x IPB 10A and IPB 10A x PB 174 were picked at 140, 145 and 150 DAA, respectively. The results indicated that peel firmness was affected by maturity stage on female fruit of IPB 10A. Maturity stage affected chemical characteristics of papaya included total soluble solids (TSS) content (IPB 10A, female fruit of PB 174, female fruit of IPB 1 x IPB 10A, and female fruit of IPB 1 x PB 174), vitamin C content (hermaphrodite fruit of 10 A, female fruit of IPB 1 x IPB 10A) and juice pH (hermaphrodite fruit of IPB 1). IPB 1 genotype can be harvested at all stadia of maturity stage. Hermaphrodite and female fruit of IPB 10 A, female fruit of PB 174, female fruit of IPB 1 x IPB 10A and female fruit of IPB 1 x PB 174 genotype would be better harvested at stadium 3 of maturity stage. Keywords: Carica papaya, papaya genotype, hermaphrodite fruit, female fruit, fruit quality, fruit maturity stage